DEMAM TIFOID: MANIFESTASI KLINIS, PILIHAN TERAPI DAN PANDANGAN DALAM ISLAM - Yelvi Levani; Aldo Dwi Prastya (Journal Medical Universitas muhammadiyah Makassar, 2020)
Typhoid fever is an acute infectious disease of the digestive system caused by the bacteria Salmonella typhi or Salmonella paratyphi. Typhoid fever is a global infectious disease in which an estimated 26.9 million cases of typhoid fever are found worldwide. Typhoid fever is especially common in developing countries because it is associated with poor sanitation. Clinical manifestations of typhoid fever that arise can vary from mild to severe symptoms. Symptoms of typhoid fever that are often found are fever, malaise, abdominal pain and constipation. Culture examination is a gold standard examination in establishing the diagnosis of typhoid fever. But this examination is rarely done. The first-line treatment option for typhoid fever is chloramphenicol. However, as the bacterial resistance to chloramphenicol increases, the main therapeutic choice for typhoid fever is the fluoroquinolone antibiotic.